Pulmonary tuberculoma: does persistent imaging lesion equals treatment failure? - Lopes, Vilma; Pinho, Joana; Rangel, Maria Adriana; Guimarães, Tânia; Carvalho, Isabel (International Journal of Contemporary Pediatrics, 2023)
Pulmonary tuberculoma is a rare but challenging entity for paediatricians, regarding diagnosis and management. Treatment course is still up for discussion since tuberculomas may persist after treatment. The authors report two paediatric cases, both recently treated for latent tuberculosis infection, admitted for investigation of a solid pulmonary nodule. In both cases the thoracic CT scan showed a nodular subpleural lesion and the biopsy revealed epithelioid cells with areas of necrosis and calcification. The diagnosis of pulmonary tuberculosis was confirmed in one case by detection of acid-fast bacilli in the smear and in the other by nucleic acid amplification test for M. tuberculosis. The patients presented good response to treatment with antituberculosis drugs, without need for surgical resection. These reports highlight the diagnostic and treatment challenges of this rare entity.